If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -15 = x Solving -15 = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -15 + -1x = x + -1x Combine like terms: x + -1x = 0 -15 + -1x = 0 Add '15' to each side of the equation. -15 + 15 + -1x = 0 + 15 Combine like terms: -15 + 15 = 0 0 + -1x = 0 + 15 -1x = 0 + 15 Combine like terms: 0 + 15 = 15 -1x = 15 Divide each side by '-1'. x = -15 Simplifying x = -15
| 46=-x | | 5x+5y= | | -x=96 | | F=10(x-70)+50 | | 3a-30=-4 | | 0.6(x+7)=24 | | -4=x^3+3x^2-9x-13 | | 3(2y-4)=5(y+3) | | -5=x^3+3x^2-9x-13 | | -4-(-3)= | | -110+22x=-1 | | 3x^2+15x-2=0 | | -16t^2+32t+32=0 | | -8+2x=6 | | -132+11x=-3 | | 4x-10x=36 | | -y+3x+6=-5 | | 3p-2=29 | | 41k=-2747 | | 9y+4y=104 | | 5x+-6=11 | | 29+n=13 | | 4x-9=-9 | | 4a-5=15 | | X-7=-19 | | 5x=4y+28 | | 2(2y-4)=3(y+5) | | 0.4(x-9)=20 | | 1.29*x=5 | | 3x+25=17x | | X^3+9X^2+20X=0 | | X^3+2X^2-2X-4=0 |